2014
DOI: 10.1242/dmm.014928
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of telomere dysfunction phenocopy skeletal changes found in human age-related osteoporosis

Abstract: A major medical challenge in the elderly is osteoporosis and the high risk of fracture. Telomere dysfunction is a cause of cellular senescence and telomere shortening, which occurs with age in cells from most human tissues, including bone. Telomere defects contribute to the pathogenesis of two progeroid disorders characterized by premature osteoporosis, Werner syndrome and dyskeratosis congenital. It is hypothesized that telomere shortening contributes to bone aging. We evaluated the skeletal phenotypes of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 68 publications
(104 reference statements)
1
31
0
1
Order By: Relevance
“…Old recipients seem to promote adipocyte differentiation preferentially, thus suggesting an environment-mediated process with aging. In mouse models of accelerated senescence, including telomere-based and other models, decreased bone formation has been reported to be associated with enhanced adipogenesis [29, 55]. However, in this study ex vivo cultures from the animals were used to establish the propensity of MPCs to differentiate into adipocytes.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Old recipients seem to promote adipocyte differentiation preferentially, thus suggesting an environment-mediated process with aging. In mouse models of accelerated senescence, including telomere-based and other models, decreased bone formation has been reported to be associated with enhanced adipogenesis [29, 55]. However, in this study ex vivo cultures from the animals were used to establish the propensity of MPCs to differentiate into adipocytes.…”
Section: 0 Discussionmentioning
confidence: 99%
“…67 Progeroid mouse models with similar genetic defects may serve as models for senile osteoporosis. 23 Current data from progeroid mouse models suggest that senile osteoporosis results from decreased bone turnover and loss of bone volume, due to defects in osteoblastic progenitor cells, osteoblastic differentiation, or osteoblastic function. As altered bone turnover is believed to play a major role in the development of senile osteoporosis, a multimodal approach is needed to gain better insight into the phenotype.…”
Section: Bone and Jointmentioning
confidence: 99%
“…Surprisingly, no significant difference was observed at the 12 week, which indicated that the calcification of neo-bone was increased with time. More importantly, lower SMI values in the pepsin group suggested that the trabecular bones adopted a more plate-like shape rather than a rod shape, a structure that resembles that observed in osteoporosis [ 34 , 35 ]. Thus, it can be concluded that the quantity and quality of regenerated bones in pepsin group are superior than other groups.…”
Section: Discussionmentioning
confidence: 99%